Intraspecific variation within Viola pubescens Regionally and Locally - Wang, Miru (Journal of Student Research, 2023)
Viola pubescens, the downy yellow violet, is a common species of plant found across the eastern North America. My research focused on the intraspecific variation within the two varieties of viola pubescens: Viola pubescens var. pubescens and var. scabriscula. I examined the climate and trait data of the two varieties across the United States (regionally), and compared the trait variation of the two varieties within Indiana (locally) between sites that are just a few miles apart. The result indicated that on a regional scale, the two varieties of viola pubescens are not of significant differences in their climate or traits. However, this can also mean that variables other than trait and environmental factors have affected the two varieties. Between local sites, differences were found between the fruit color and hairiness. The local site, Lower Cascades, only produced green fruit with no hair. While other sites showed variation in fruit color (ranging from green to purple) and hairiness (amount of hair present on the fruit), Lower Cascades have no variation in its fruit phenotype. This could lead to further study of the genetic variation across viola pubescens and its varieties. By having an exceeding understanding on the strucutre of the variation within viola pubescens, we can better visualize the scale at which plants are adapting and responding to their environment.